Keto acid metabolites of branched-chain amino acids inhibit oxidative stress-induced necrosis and attenuate myocardial ischemia–reperfusion injury. (December 2016) - Dong, Weibing; Zhou, Meiyi; Dong, Mei; Pan, Bangfen; Liu, Yunxia; Shao, Jing; Gu, Xiaoping; Huang, Ying; Li, Guangping; Wang, Yibin; Sun, Haipeng
Abstract: Branched chain α-keto acids (BCKAs) are endogenous metabolites of branched-chain amino acids (BCAAs). BCAA and BCKA are significantly elevated in pathologically stressed heart and contribute to chronic pathological remodeling and dysfunction. However, their direct impact on acute cardiac injury is unknown. Here, we demonstrated that elevated BCKAs significantly attenuated ischemia–reperfusion (I/R) injury and preserved post I/R function in isolated mouse hearts. BCKAs protected cardiomyocytes from oxidative stress-induced cell death in vitro. Mechanistically, BCKA protected oxidative stress induced cell death by inhibiting necrosis without affecting apoptosis or autophagy. Furthermore, BCKAs, but not BCAAs, protected mitochondria and energy production from oxidative injury. Finally, administration of BCKAs during reperfusion was sufficient to significantly attenuate cardiac I/R injury. These findings uncover an unexpected role of BCAA metabolites in cardioprotection against acute ischemia/reperfusion injury, and demonstrate the potential use of BCKA treatment to preserve ischemic tissue during reperfusion. Highlights: BCKAs attenuate ischemia–reperfusion injury and preserve heart function. BCKAs protect cardiomyocytes from oxidative stress-induced necrosis. BCKAs protect mitochondria and energy production against oxidative injury. BCKA administration during reperfusion significantly attenuates cardiac I/R injury.